Maternal air temperature exposure and risk of small vulnerable newborn: Identifying critical windows - Mingzhao Huang; Jian Fang; Yaqi Zhang; Luli Xu; Xiya Qin; Kai Chen; Zhiguo Xia; Jun Li; Lianting Hu; Xiaofeng Mu; Xiaoxuan Fan; Youjie Wang; et al. (Ecotoxicology and Environmental Safety)
Background: Small vulnerable newborn (SVN), defined as preterm birth (PTB), small for gestational age (SGA), or low birth weight (LBW), remains a global health challenge. While prenatal temperature exposure may influence pregnancy outcomes, existing trimester-level analyses lack temporal precision to detect sensitive gestational windows. This population-based study aims to explore the relationship between temperature and SVN over time and identify critical exposure periods with weekly resolution. Methods: Using a retrospective cohort of 1,129,572 singleton births (2011–2022) in Wuhan, China, we linked daily ambient temperature data at 1-km² resolution to maternal residential coordinates. Extended distributed lag non-linear models (Extended-DLNMs) combined with logistic regression examined associations between weekly temperature exposure and SVN outcomes. Results: Of the births, 14.5 % were classified as SVN (7.49 % PTB, 4.66 % LBW, 7.58 % SGA). Exposure to heat (28.8°C v.s. 18.6°C) and cold (5.3°C v.s. 18.6°C) during pregnancy was associated with increased SVN risks, primarily driven by PTB and LBW. Heat exposure during weeks 10–23 and 34–37 increased PTB risk, peaking at week 37 (OR: 1.11, 95 % CI: 1.09–1.13). Cold exposure during weeks 1–13 and 22–33 increased PTB risk, most notably at week 28 (OR: 1.09, 95 % CI: 1.07–1.10). For LBW, heat exposure during weeks 9–24 and 37–42 was associated with increased risks, strongest at week 42 (OR: 1.19, 95 % CI: 1.16–1.21). Cold exposure during weeks 1–6 and 23–34 correlated with elevated LBW risks, particularly at week 29 (OR: 1.08, 95 % CI: 1.05–1.11). Conclusions: While the overall exposure-response relationship exhibits a U-shaped pattern throughout gestation, our findings reveal substantial heterogeneity in temperature sensitivity across developmental windows. Some gestational stages are more susceptible to heat, whereas others exhibit increased vulnerability to cold. Further mechanistic research is warranted to elucidate the placental and fetal adaptation pathways under temperature extremes.